Hubungan Kebiasaan Olahraga dengan Keluhan Nyeri Punggung Bawah (Low Back Pain) pada Penjahit - Annissa Annissa; Alvi Annissa (Universitas Faletehan, 2025)
A preliminary study conducted on 10 tailors in Cilegon District showed that 60% of them suffered from moderate low back pain which could reduce their productivity. The purpose of this study is to find out the factors related to lower back pain complaints. This study used a cross-sectional design with a sample size of 70 tailors in Cilegon District. The sampling technique in this study was carried out using the accidental sampling method. Data were analysed through univariate and bivariate analysis, using the chi square test. The results of the analysis showed a relationship between age (P value=0.006), back posture (P value=0.002), and exercise habits (P value=0.015) with moderate low back pain complaints. There was no significant relationship between sitting duration (P value=0.511) and moderate low back pain complaints. The results showed that majority of respondents felt complaints of LBP in the moderate category (57.1%). Tailors should pay more attention to their back posture when sewing and do stretching and exercising.